Differences in Onomatopoeia Used by Japanese Men and Women in Social Media Twitter - Annnastasya Prima Nadia Salsabila (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
Japanese onomatopoeia, often referred to as giongo and gitaigo, is a word used to describe a sound or situation where the meaning of the word is derived from it's sounds or what it describes. While there have been many studies on Japanese onomatopoeia, there have not been many studies on the comparison of differences in usage. This study looked at the onomatopoeia used on Twitter by Japanese men and women in their 20s and 30s, and there were three main points that emerged from the study. First, compared to the same number of people posting at a single point in time, women were more likely than men to use onomatopoeia on Twitter. Secondly, for both men and women, the most commonly used onomatopoeia is めちゃめちゃ(mechamecha). Women use どきどき(dokidoki) more, while men use わくわく(wakuwaku) more. In addition, there was a significant difference in the use of わくわく(wakuwaku) between men and women. Finally, the most commonly used part of speech for onomatopoeia on Twitter was 副詞(fukushi/adverb), both for men and for women. While there are differences in how men and women use onomatopoeia, there are also some similarities.